Community field-centric trust-based access control model - Zhi-qiang YAO; Jin-bo XIONG; Jian-feng MA; Qi LI; Xi-meng LIU (Tongxin xuebao, 2013)
Context-aware interaction and cooperation among agents provids digital community services.However,it also brings new problems of secure access.A novel community field-centric trust-based access control model (referred to as the CTBAC) was developed by thoroughly considering both the trust level of agent and the cooperation among agents inside and outside of community fields in digital commun ty.There are two novel ingredients.Firstly,a community field was established in terms of agent’s own contexts and trust certificate.Thus,the trust level could be dynamically adjusted based on the sessions.Secondly,the activation and use of access control permissions according to the match relationship between the trust level of agents and trust threshold.The proposed CTBAC model was compared to several access control models and its effectiveness in both dynamic permission control and security protection was demonstrated.